ANALISIS KINERJA REKSADANA SAHAM DENGAN MENGGUNAKAN METODE SHARPE DAN TREYNOR (STUDI PADA REKSADANA SAHAM YANG TERDAFTAR DI OTORITAS JASA KEUANGAN TAHUN 2014-2016) - Yuliana, Dian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The development of mutual funds investment management in Indonesia has experienced good growth. One of the investment products that continues to attract the community during 2014 to 2016 is stock funds. Stock funds have both high returns and high risk. Investors should know well the return and risk profile of the portfolio to be selected. A way to find out the performance evaluation of a portfolio that measures returns and risks is by using Risk Adjusted method. There are 2 (two) methods that are part of Risk Adjusted namely Sharpe and Treynor methods.The purpose of this research is to concludethe performance of stock funds and to give information about the performance of stock fund compared to performance of IHSG based on Sharpe and Treynor method. This research is a descriptive quantitative in nature. The population in this study are all active stock funds which is registered in the Financial Services Authority for the period 2014 to 2016. This study using purposive sampling as sampling method with sample size of 78 stock funds. The research using secondary data from publication reports of Financial Services Authority, Indonesia Stock Exchange, Bank Indonesia and Kontan Data. During the observation period (2014-2016), there is no stock fund that able to consistently outperform, but among other stock funds, there is stock fund which able to outperform compared to BI Rate and IHSG for 3 years and consistently ranked the top 10 best stock fund performance. The stock fund is Hpam Ultima Equity, therefore it is worth to invest.Keywords: Mutual Fund Performance, Stock Fund, Sharpe Method, Treynor MethodÂ